The Final Step in Molybdenum Cofactor Biosynthesis—A Historical View - Ralf R. Mendel; Kevin D. Oliphant (Molecules)
Molybdenum (Mo) is an essential micronutrient across all kingdoms of life, where it functions as a key component of the active centers of molybdenum-dependent enzymes. For these enzymes to gain catalytic activity, Mo must be complexed with a pterin scaffold to form the molybdenum cofactor (Moco). The final step of Moco biosynthesis is catalyzed by the enzyme Mo-insertase. This review focuses on eukaryotic Mo-insertases, with an emphasis on those found in plants and mammals, which have been instrumental in advancing the understanding of Mo biochemistry. Additionally, a historical perspective is provided, tracing the discovery of Mo-insertase from the early 1960s to the detailed characterization of its reaction mechanism in 2021. This review also highlights key milestones in the study of Mo-insertase, including mutant characterization, gene cloning, structural elucidation at the atomic level, functional domain assignment, and the spatial organization of the enzyme within cellular protein networks.